CCN2/CTGF tip the balance of growth factors towards TGF-β2 in primary open-angle glaucoma - Dillinger, Andrea E.; Kuespert, Sabrina; Seleem, Amin A.; Neuendorf, Jakob; Schneider, Magdalena; Fuchshofer, Rudolf (Frontiers in Molecular Biosciences, 2023)
TGF-β2 is the predominant TGF-β isoform within the eye. One function of TGF-β2 is to provide the eye with immune protection against intraocular inflammation. The beneficial function of TGF-β2 within the eye must be under a tight control of a network of different factors. A disbalance of the network can result in different eye diseases. In Primary Open-Angle Glaucoma (POAG), one of the leading causes of irreversible blindness worldwide, TGF-β2 is significantly elevated in the aqueous humor and antagonistic molecules like BMPs are reduced. The changes provoke an altering of the quantity and quality of the extracellular matrix and the actin cytoskeleton in the outflow tissues leading to an increased outflow resistance and thereby to an increased intraocular pressure (IOP), the major risk factor for POAG. The pathologic effect of TGF-β2 in POAG is mainly meditated by CCN2/CTGF. CCN2/CTGF can modulate TGF-β and BMP signaling by direct binding. The eye specific overexpression of CCN2/CTGF caused an increase in IOP and led to a loss of axons, the hallmark of POAG. CCN2/CTGF appears to play a critical role in the homeostatic balance of the eye, so we investigated if CCN2/CTGF can modulate BMP and TGF-β signaling pathway in the outflow tissues. To this end, we analyzed the direct effect of CCN2/CTGF on both signaling pathways in two transgenic mouse models with a moderate (βB1-CTGF1) and a high CCN2/CTGF (βB1-CTGF6) overexpression and in immortalized human trabecular meshwork (HTM) cells. Additionally, we investigate whether CCN2/CTGF mediates TGF-β effects via different pathways. We observed developmental malformations in the ciliary body in the βB1-CTGF6 caused by an inhibition of the BMP signaling pathway. In the βB1-CTGF1, we detected a dysregulation of the BMP and TGF-β signaling pathways, with a reduced BMP activity and increased TGF-β signaling. The direct CCN2/CTGF effect on BMP and TGF-β signaling was shown in immortalized HTM cells. Finally, CCN2/CTGF mediated the effects on TGF-β via the RhoA/ROCK and ERK signaling in immortalized HTM cells. We conclude that CCN2/CTGF functions as a modulator of the homeostatic balance of BMP and TGF-β signaling pathway, which is shifted in POAG.